AB0574 Prevalence of hla-drb1 in psoriatic arthritis, psoriasis and rheumatoid arthritis: comparison with healthy controls. (23rd January 2014) - Bejerano, C.; Blanco, E. A.; Pinto-Tasende, J.; Pértega, S.; Rego, I.; Oreiro, N.; Lois, A.; De Toro, J.; Blanco, F. J.; Fernández-Sueiro, J. L.
Abstract : Background: Major Histocompatibility Complex (HLA) has shown consistent linkage with Psoriasis, Rheumatoid Arthritis (RA) and psoriatic arthritis (PsA) in multiple studies. The complex patterns of inheritance suggest that multiple alleles of different genes HLA are required for susceptibility to these diseases. Objectives: To study the frequency of HLA-DRB1 genes (including shared epitope, SE) in psoriasis, PsA and RA compared with healthy controls. Methods: HLA-DRB1 genotyping was performed by PCR-SSP (Sequence Specific Primer) in DNA samples from 625 Caucasian subjects in Northwest Spain. Frequencies of HLA-DRB1 alleles were determined in patients with psoriasis (n = 115), PsA (n = 163), RA (n = 170) and were compared with those of healthy controls (n = 177). The odds ratio (OR) was performed to analyzed association between alleles and disease. We compared differences between individual carriers and non-carriers of the alleles by using Chi-square and Fisher's exact tests. Statistical significance was p < 0, 05. Results: With respect to healthy control there was no significant differences in the prevalence of HLA-DRB1 * 10 and * 14. HLA-DRB1 * 02, * 05 and * 06 were more frequent in controls (p <0.0001). HLA-DRB1 * 03 was less frequent in psoriasis and PsA (Table 1 ). HLA-DRB1 * 07 was less frequent in RA. HLA-DRB1 * 13 and HLA-DRB1 * 17 were more common in psoriasis and PsA. HLA-DRB1 * 15 was more common in psoriasis and RA. Shared epitope (SE) alleles HLA-DRB1 * 0101 and *0401 were more frequent in RA and * 0102 in RA and Psoriasis. Conclusions: Conclusions: In our study, Psoriasis and PsA are associated with HLA-DRB1 * 13 and * 17. Presence of HLA-DRB1 * 03 is associated with lower risk of psoriasis and PsA. HLA-DRB1 * 07 isassociated with lower risk of RA. Finally, SE alleles 0101, * 0102 and * 0401 are not significantly associated with psoriatic arthritis. Acknowledgements: The authors thank José Luis Fernández-Sueiro for him hard work and dedication. Rest in peace. Disclosure of Interest: None Declared